2001
DOI: 10.1128/iai.69.4.2714-2717.2001
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Vaccine for Tuberculosis

Abstract: An effective new vaccine for the control of tuberculosis is badly needed. While current research attempts to improve vaccination are concentrating on new prophylactic or immunotherapeutic vaccines, virtually no emphasis has been placed on boosting individuals already inoculated with Mycobacterium bovis BCG. It is shown here that mice vaccinated with BCG gradually lose their capacity to resist an aerosol challenge infection as they age. However, if these mice are inoculated with the 30-kDa mycolyl transferase A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 17 publications
2
60
0
Order By: Relevance
“…A combination of both strains, therefore, may be considered for replacing conventional BCG for vaccination of newborns. Recently, several subunit vaccine candidates have been described, which can be used to boost immune responses induced by BCG prime (38)(39)(40)(41)(42). It is tempting to assume that a combination of priming with improved BCG such as ∆ureC hly + rBCG and boosting with the most efficacious subunit vaccine would provide more powerful intervention measures against one of the major threats among infectious diseases, tuberculosis.…”
Section: Figurementioning
confidence: 99%
“…A combination of both strains, therefore, may be considered for replacing conventional BCG for vaccination of newborns. Recently, several subunit vaccine candidates have been described, which can be used to boost immune responses induced by BCG prime (38)(39)(40)(41)(42). It is tempting to assume that a combination of priming with improved BCG such as ∆ureC hly + rBCG and boosting with the most efficacious subunit vaccine would provide more powerful intervention measures against one of the major threats among infectious diseases, tuberculosis.…”
Section: Figurementioning
confidence: 99%
“…Consequently, new vaccines will be tested and potentially administered in previously BCG-vaccinated individuals. This need is addressed by the prime-boost approach that we have tested (8,32,33). In our experiments, the boosting of BCG with Mtb72FϩAS01B resulted in a significant reduction in the inflammatory response (P was 0.02 for WBC in CSF), less weight loss as well as a reduced bacillary load, and attenuated pathology in the brains of infected rabbits (Table 1).…”
Section: Discussionmentioning
confidence: 92%
“…Animals boosted with Mtb72F-DNA showed better resolution and earlier healing of lung lesions. One of the current views in TB vaccine design is that existing memory immunity should be targeted with a specific antigen that is recognized by a sufficient number of memory CD4 ϩ T cells (8). Recently, a few prime-boost studies, using Rv3407 DNA (33), Ag85A (8), or MVA85A (modified vaccinia virus Ankara expressing antigen 85A) (32) as a boost, appeared to achieve superior protection compared to that conferred by BCG vaccination alone in mice and improved immunity in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments using protein subunits in animals previously vaccinated with BCG (BCG+), and using prime-boost protocols give very good results [24]. These experiments used Ag85A, because it was previously demonstrated that most CD4 T cells accumulating in the lungs of memory-immune mice after challenge recognise this antigen.…”
Section: Boosting Bcg Vaccinementioning
confidence: 99%